2008
DOI: 10.1016/j.cmet.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Functional Relay between Insulin Receptor Substrate 1 and 2 in Hepatic Insulin Signaling during Fasting and Feeding

Abstract: Insulin receptor substrate (Irs) mediates metabolic actions of insulin. Here, we show that hepatic Irs1 and Irs2 function in a distinct manner in the regulation of glucose homeostasis. The PI3K activity associated with Irs2 began to increase during fasting, reached its peak immediately after refeeding, and decreased rapidly thereafter. By contrast, the PI3K activity associated with Irs1 began to increase a few hours after refeeding and reached its peak thereafter. The data indicate that Irs2 mainly functions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
209
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 41 publications
13
209
0
Order By: Relevance
“…The reverse-transcription reaction was carried out with a high-capacity cDNA reverse transcription kit (Applied Biosystems). Quantitative PCR analyses using TaqMan assays were performed as previously described (37). The relative expression levels were normalized by measurement of the amount of cyclophilin in each sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse-transcription reaction was carried out with a high-capacity cDNA reverse transcription kit (Applied Biosystems). Quantitative PCR analyses using TaqMan assays were performed as previously described (37). The relative expression levels were normalized by measurement of the amount of cyclophilin in each sample.…”
Section: Methodsmentioning
confidence: 99%
“…injections of glucose after an overnight fast. Blood glucose levels were measured using a Glutest sensor (Sanwa Chemical) at the indicated time points, and the plasma insulin levels were measured using a RIA kit (Biotrek), as previously described (37).…”
Section: Methodsmentioning
confidence: 99%
“…This is thought to be compensation for the loss of Irs-1 function described e.g. in Kubota et al (2008) and Dobrzyn et al (2010). (iii) A decrease in the level of expression of Pdx-1 reduced Irs-2 expression, and this effect surpassed the reverse effect described above in (ii) as demonstrated in the double knockdown cells (double knockdown cell lines in Fig.…”
Section: Discussionmentioning
confidence: 71%
“…GSIS is a combination of glucose reception and insulin secretion functions. A number of studies have examined the genetic basis of diabetes and identified specific genes for insulin production (Melloul et al 2001), insulin reception (Kubota et al 2008;Guo et al 2009;Dobrzyn et al 2010), and GSIS (Pal 2009;Bennett et al 2010). It has been speculated that the genes for these various roles are functionally linked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation